A Numerical Investigation of Automotive Lambda Sensor to Improve the Life Span of the Sensor using CFD. Issue 1 (September 2020) - Aravind, S; Ragupathi, P; Kumar, D Sathish; Vignesh, G
Abstract : Abstract The modern technology has tremendously improved the controlling technologies for fuel injection system and the emission of various harmful greenhouse gases. For detecting oxygen level in the combustion chamber and exhaust gases, a sensor named lambda sensor is used in most of the automobiles. In this paper, a numerical simulation of this lambda sensor was carried out to improve the life span of the sensors protection wall by changing its design with the help of computational fluid dynamics techniques. The simulation results showed that exhaust gas entering the sensor with a pressure range reduced by about 1.41% in comparison to its prevailing design. At the central zone of the sensor, the pressure value reduced by 9.81% with the design modification performed in the protection layer of the lambda sensor. Similarly, the exhaust gas leaving the sensor showed a 6.45% pressure drop in par with the prevailing model. The velocity and temperature of the exhaust gas were the other parameters studied. The simulation results of improved protection layer design when compared to the prevailing model indicated that, the exhaust gas velocity at the inlet and central zone of the sensor was reduced by 19.37% and 17.1% respectively. The exhaust gas temperature showed a drop of 15% in the central zone of the sensor for the new improved model. Thus, from the simulation results it can be stated that, the design modification done in the protection layer of the lambda sensor will positively improvise the life span of the sensor from present life time of 2.5 Lakh kilometres or 15 years.